Penerapan Informasi Akuntansi Diferensial Dalam Pengambilan Keputusan Manajemen Pada Kios Martabak/Malabar Mas Narto - Muchtar, Maria Gabrielle; Sondakh, Jullie J; Rondonuwu, Sintje (Universitas Sam Ratulangi, 2024)
Differential accounting information is one of the information needed by a company in planning and decision making such as accepting or rejecting special orders that will help the company in this case Kios Martabak/Malabar Mas Narto in receiving special orders. The purpose of this study is to determine the application of differential accounting information in management decision making to accept or reject special orders on Kios Martabak/Malabar Mas Narto The type of research used in this study is qualitative research with a descriptive approach and data analysis used in this study, namely the descriptive method. The results showed that the alternative of receiving special orders became a decision that companies could make. This is done based on a comparison between differential income which is greater than differential costs, resulting in an additional profit of Rp.11.826.000 obtained from special orders. Therefore, differential accounting information such as differential income, differential costs and differential profit can help companies to know whether special orders are acceptable or not and can provide additional profits or not. Keywords: Differential Accounting Information, Decision Making, Special Orders